Macrophages promote Fibrinogenesis during kidney injury - Oh, Hanna; Kwon, Ohbin; Kong, Min Jung; Park, Kwon Moo; Baek, Jea-Hyun (Frontiers in Medicine, 2023)
Macrophages (Mø) are widely considered fundamental in the development of kidney fibrosis since Mø accumulation commonly aggravates kidney fibrosis, while Mø depletion mitigates it. Although many studies have aimed to elucidate Mø-dependent mechanisms linked to kidney fibrosis and have suggested various mechanisms, the proposed roles have been mostly passive, indirect, and non-unique to Mø. Therefore, the molecular mechanism of how Mø directly promote kidney fibrosis is not fully understood. Recent evidence suggests that Mø produce coagulation factors under diverse pathologic conditions. Notably, coagulation factors mediate fibrinogenesis and contribute to fibrosis. Thus, we hypothesized that kidney Mø express coagulation factors that contribute to the provisional matrix formation during acute kidney injury (AKI). To test our hypothesis, we probed for Mø-derived coagulation factors after kidney injury and uncovered that both infiltrating and kidney-resident Mø produce non-redundant coagulation factors in AKI and chronic kidney disease (CKD). We also identified F13a1, which catalyzes the final step of the coagulation cascade, as the most strongly upregulated coagulation factor in murine and human kidney Mø during AKI and CKD. Our in vitro experiments revealed that the upregulation of coagulation factors in Mø occurs in a Ca2+-dependent manner. Taken together, our study demonstrates that kidney Mø populations express key coagulation factors following local injury, suggesting a novel effector mechanism of Mø contributing to kidney fibrosis.